Is intraoperative supplementation of dextrose essential for infants undergoing facial cleft surgeries? - Sunil Rajan; Kaushik Barua; Pulak Tosh; Lakshmi Kumar (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Dextrose is commonly added to the intraoperative maintenance fluids of pediatric patients. The primary objective was to evaluate the effect of addition of 1% dextrose to Ringer's lactate (RL) on blood glucose levels in infants undergoing facial cleft surgeries. Material and Methods: This prospective, randomized, single blinded study was conducted in forty infants undergoing either cheiloplasty or palatoplasty. Random blood sugar (RBS) was assessed using a glucometer after induction of anaesthesia, and at 1 and 2 hours later. Group R received RL and Group D received RL with 1% dextrose as intraoperative maintenance fluid. Hypoglycemia was defined as RBS <70 mg/dL and hyperglycemia as RBS >150 mg/dL. Results: Baseline RBS levels and those at 60 min and 120 min post-induction were comparable in both groups. The increase in blood sugar levels from baseline to 60 min and to 120 min in each group was significant. Incidence of hyperglycemia was comparable in both groups. There were no episodes of hypoglycemia, intraoperatively. Conclusion: Use of Ringer lactate alone or with addition of 1% dextrose resulted in comparable intraoperative blood sugar levels when used as maintenance fluid in infants undergoing facial cleft surgeries.